(untitled) (Bangladesh Heart Journal, 2018)
Background: Acute myocardial infarction (AMI) is one of the leading causes of death and disability all over the world. Primary percutaneous coronary intervention (PCI) is the treatment of choice for patients with acute ST segment elevation myocardial infarction (STEMI). Primary PCI is being increasingly done in our country also. But the factor influencing the outcome of primary PCI in our setting are mostly unknown. The present study was conducted to investigate factors that influencing the short term outcomes of primary PCI. Materials and methods: This prospective observational study was conducted from September 2014 to January 2016in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka. 48 patients were selected by purposive sampling. Patients with acute STEMI treated with primary PCI were included in the study based on inclusion and exclusion criteria. Effect of factors including advanced age, male sex, diabetes mellitus, hypertension, dyslipidemia, serum creatinine, left ventricular ejection fraction, anterior myocardial infarction (MI), thrombolysis in myocardial infarction (TIMI) flow, multi vessel disease, angiographic severity score (Leaman score), thrombus aspiration, door to balloon time and total ischemic time on major adverse cardiac events (MACE) i.e. death, post procedural MI, target vessel revascularization (TVR), stroke as well as, on other adverse events like heart failure, cardiogenic shock, major bleeding, significant arrhythmia and stent thrombosis were studied. Results: The overall incidence of MACE was 2.1%, major bleeding 2.1%, heart failure 4.2% and cardiogenic shock 2.1%. In multivariate analysis, the factors independently influencing the adverse short term outcomes (MACE and other adverse events) were diabetes mellitus (odds ratio (OR) 2.55, 95% confidence interval (CI) 1.180 to 4.124, p=0.02), anterior MI (OR 1.48, 95% CI 1.020 to 1.926, p=0.04), total ischaemic time (OR 1.49, 95% CI 1.044 to 2.444, p=0.04), multivessel coronary artery disease (OR 1.77, 95% CI 1.26 to 3.261, p=0.03) and Leaman score (OR 2.5, 95% CI 1.100-4.504, p=.03). Conclusion: According to our finding, diabetes mellitus, anterior myocardial infarction, total ischemic time, multivessel coronary artery disease and high Leaman score are predictors of adverse short term outcomes of primary PCI Bangladesh Heart Journal 2018; 33(2) : 112-120